2011
DOI: 10.1051/ijmqe/2011007
|View full text |Cite
|
Sign up to set email alerts
|

Copilot Pro®: A full method for the steering of the machining

Abstract: Abstract. Copilot Pro is a method for the initial and regular machine-tools setup, developed by the Symme laboratory of the Savoy University and by the Technical Center of Industries of Screw-machining (Ctdec) in France. Its first step is the organization of the different machining operations, in setup steps, themselves subdivided into measuring steps. The second step consists in determining the manufacturing dimensions to measure at the end of each measuring step. Finally, the third step consists in linking t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The authors Bourdet, 1982 andAnselmetti andBourdet, 1993 have shown that if we can act on the correctors of the machine to reduce the difference between the theoretical part and the machined part, it can also be reduced by acting on the optimal dimensions chosen intelligently. The authors Goldschmidt 2009 andPairel et al, 2011 implemented the Copilot-Pro® methodology that allows the adjustment of all cutting tools, including roughing tools. Their method determines the "range of setting" or the "range of monitoring" in a manufacturing step and allows determining the manufacturing dimensions to be measured to adjust a maximum of cutting tools per step.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors Bourdet, 1982 andAnselmetti andBourdet, 1993 have shown that if we can act on the correctors of the machine to reduce the difference between the theoretical part and the machined part, it can also be reduced by acting on the optimal dimensions chosen intelligently. The authors Goldschmidt 2009 andPairel et al, 2011 implemented the Copilot-Pro® methodology that allows the adjustment of all cutting tools, including roughing tools. Their method determines the "range of setting" or the "range of monitoring" in a manufacturing step and allows determining the manufacturing dimensions to be measured to adjust a maximum of cutting tools per step.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%
“…There are methods in the literature to determine the manufacturing dimensions necessary for the good adjustment of the machine, but the methods proposed by Goldschmidt 2009 andPairel et al, 2011 differs in that because these dimensions are determined taking into account the constraints related to manufacturing process. The authors Goldschmidt et al, 2007, andBoukar et al, 2012, conscious of the interest offered by the geometric tolerancing to ensure the conformity of the products, exploited this tolerance for setting the machines.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%
“…Martin et al [9] showed that the geometrical adjustment of manufacturing defects could be done using the principle of the small displacements torsor. The authors Pairel et al [10,11] and Goldschmidt [12] proposed a method called Copilot-Pro which adjusts all cutting tools for finishing and roughing. The method is to adjust the machine by measuring the most relevant manufacturing dimensions, determined from the plan of process adjustment.…”
Section: Introductionmentioning
confidence: 99%